The “hot cross bun sign” in patients with autoimmune cerebellar ataxia: A case report and literature review - Liu, Mange; Ren, Haitao; Lin, Nan; Tan, Ying; Fan, Siyuan; Guan, Hongzhi (Frontiers in Neurology, 2022)
Objectives The “hot cross bun sign” (HCBs) on magnetic resonance imaging (MRI) has been initially considered specific for multiple system atrophy with cerebellar features. However, a number of other conditions have since been described, which may be associated with this imaging sign. We herein describe a patient with anti-Ri and paraneoplastic cerebellar ataxia, and review the association of the HCBs on imaging with various neurological autoimmune conditions. Methods We report a 40-year-old woman with anti-Ri-associated paraneoplastic neurological syndrome and breast carcinoma, in whom brain MRI revealed the HCBs late in the disease course. We also reviewed similar cases reported in the literature. Results The patient presented with cerebellar ataxia, polyneuropathy, and pyramidal signs. Although brain MRI was initially unremarkable, the HCBs and T2-weighted hyperintensity of the bilateral middle cerebellar peduncles were observed at later follow-up. Anti-Ri was detected in the serum and cerebrospinal fluid. Breast adenocarcinoma was confirmed via an axillary lymph node biopsy. Her symptoms partially resolved after the first corticosteroid pulse. However, subsequent immunotherapy and tumor treatments were ineffective. Four autoimmune cerebellar ataxia cases with the HCBs (two paraneoplastic and two non-paraneoplastic) were identified in the literature. Discussion The HCBs can be associated with paraneoplastic and non-paraneoplastic cerebellar ataxia, which may reflect neurodegeneration secondary to autoimmune injury. Thus, the HCBs should not be considered a contraindication for autoimmune cerebellar syndrome.